Barriers and facilitators to successful implementation of sustainable school meals: a qualitative study of the OPTIMAT™-intervention - Patricia Eustachio Colombo; Liselotte Schäfer Elinder; Emma Patterson; Alexandr Parlesak; Anna Karin Lindroos; Susanne Andermo (BMC, 2021)
Abstract Background There is an urgent need to align human diets with goals for environmental sustainability and population health. The OPTIMAT™-intervention study was developed to implement and evaluate a nutritionally adequate and climate-friendly 4-week lunch menu in Swedish primary schools. This study aimed to explore pupils' and kitchen staff's experiences of the intervention and to identify barriers and facilitators to successful implementation of sustainable school meals. Methods An inductive manifest qualitative method was used. Nine focus group discussions (FGDs) were conducted, six with pupils in grades 5 (ages 10-11) and 8 (ages 14-15) (n = 29) and three with kitchen staff (n = 13). Data were analyzed using qualitative content analysis. Results Five main categories and 11 subcategories at a manifest level emerged. The five main categories were: 1) Experiences with the new menu, unfolding variations in how the new menu was received and kitchen staff's experiences of working with it; 2) The meaning of diet sustainability, comprising pupils' and kitchen staff's perceptions about diet sustainability as a concept and part of their everyday lives; 3) Factors influencing plant-based food acceptance, covering aspects such as the influence of sensory factors, habits and peer pressure; 4) Opportunities to increase plant-based eating, including factors related to pupils' and kitchen staff's ideas for how to increase plant-based food acceptance; and 5) Need for a supportive environment to achieve dietary change, comprising pupils' and kitchen staff's thoughts on the importance of more knowledge, resources and involvement of stakeholders to eat more plant-based meals in schools. Conclusions Successful implementation of sustainable school meals would require more knowledge among pupils and kitchen staff. Staff also need more training in cooking of sustainable meals. Barriers among pupils could be tackled by introducing new plant-based meals more gradually and by more carefully considering the seasoning, naming and aesthetics of dishes. An increased leadership support for change and involvement of stakeholders from multiple levels within society will be key in the transition to sustainable school meals at scale. Trial registration The trial registration for the OPTIMAT™-intervention may be found at clinicaltrials.gov ( NCT04168632 Fostering Healthy and Sustainable Diets Through School Meals (OPTIMAT)).